Menelusuri dampak sosial dan ekonomi kemiskinan: Tantangan dan solusi di era modern - Azarina, Melsa Nur Izzati (Maliki Interdisciplinary Journal, 2024)
Poverty has become a complex and very disturbing problem throughout the world. This poverty has a significant social impact on individuals, families and society as a whole. Especially in the current modern era, the impact of social and economic poverty is increasingly becoming a major concern because it is becoming more widespread and deeper in a country’s society and economy. Apart from that, poverty also has a big impact on a country’s economy, poverty can hinder a country’s economy, reduce labor productivity and weaken the economy. This research method uses literature observation (library research) or what is often referred to as library research or library study. This research explains that poverty is not just a lack of material conditions, but also a multidimensional phenomenon that has deep social and economic impacts. Describes how poverty affects various aspects of society and the economy.